Addressing Ocean Acidification within the Framework of International law - Abed, Mustafa (Journal of Legal Sciences, 2025)
The oceans contribute a fundamental role in regulating the Earth’s climate by absorbing heat and almost a third of the total carbon from the atmosphere. As a result of human activity, the percentage of greenhouse gases in this atmosphere increased, and then the percentage of what the oceans absorbed from them increased, because ocean acidification and climate change are two phenomena that are closely interrelated. Close, because carbon dioxide is the largest greenhouse gas in terms of volume, and it is also the main cause of ocean acidification. This means that mitigating global warming by reducing carbon dioxide concentrations in the atmosphere will lead directly to mitigating the impact of ocean acidification. In this research, we will discuss the available methods for dealing with ocean acidification in international law, as it is one of the most future threats to the marine environment. Some international agreements on the environment and research initiatives adopted by international organizations in this regard.